John Adams - McCullough, David G. (Waterville, ME : Thorndike Press, 2001)
Presents a biography portraying John Adams as a brilliant, fiercely independent Yankee patriot who spared nothing in his zeal for the American Revolution and then rose to become the second president of the United States. Provided by the publisher.
Incudes bibliographic references (p. 999-1121) and index.
Keywords: Adams, John, -- 1735-1826.; Presidents -- United States -- Biography; Large type books; United States -- Politics and government -- 1775-1783.; United States -- Politics and government -- 1783-1809.